Learning by Almost Doing: New Education Methods for Learning about Driving Automation Systems - Bengtsson, Adam; Vestberg, Alfred (My University, 2023)
Driving automation systems (DAS) in cars are systems that can take over parts of the driving control from the driver. There are standardised ways of categorising five levels of automation (LoAs) by defining the control of the car and the where the responsibility of the car lies. There is a problem for driver’s and automakers that some drivers are having trouble understanding DAS in the correct way. This could increase the risk that some drivers misuse the DAS because they fail to understand the limitations and functions to a certain degree which causes some safety concerns. There is mode confusion which increases risk for some drivers to misunderstand the modes of automation in their cars. DAS are getting developed even further which leads to more complexity for the driver. It is in automakers interest to have their drivers use their systems as intended but it is also becoming a demand from outside authorities to provide effective education as DAS is becoming more common and advanced. To support this, the methods of educating drivers needs to be developed in order to be more efficient and motivating in according to human learning behaviour. Other studies have researched ways to educate drivers by suggesting new methods which have been successful. What this thesis researched was a comparative study of education methods to create a base for what a good education needs in term of being effective and motivating. This was done by creating education concepts which applies different methods of education which were then tested on people to see if they understood the content. A literature study was first done to establish a starting ground in the subject. A focus on a learning theory in constructivism was used which says that learning is constructed in an individual when they actively participate. To achieve an effective learning method, it needs to create motivation within the learner who will otherwise be bored and find something else to occupy their mind. A certain level of immersion and engagement is required according to learning theory to create an effective learning method. Other methods for creating good motivation within the learner is gamification. It uses elements from games designed to keep the player feeling motivated and rewarded for their work. Two new conceptual education methods for DAS were created and tested. One concept made for simulating the environment of driving in a car with DAS which involves the learner on an active level. They get to watch scenarios from a drivers POV where DAS are relevant. They affect the outcome by making choices that results in different outcomes. The other concept uses gamification in a quiz format where the user progresses through higher levels by completing questions. They were rewarded and could track their progress. In both concepts they got feedback for each correct or incorrect answer resulting in them learning something new. These concepts were used in a user test with a printed user manual as a comparative baseline method. The test participants were provided with an educational material (Scenario concept, Quiz concept, or User manual) that educated them in DAS. The test involved observation of simulator driving, survey questions, and interview questions. The scenario concept performed the best in our user test, with the quiz coming second. The scenario concept had good performance when using DAS in the simulator but also on a theoretical knowledge level. It showed that a good method for education is to immerse the learner in real environments where they are actively participating and affecting the outcome. It creates both an effective learning method but also a motivating one where the learner enjoys doing it. We have created design guidelines with the help of the findings from the concepts which describe how to design effective and motivating educational material for DAS.